2013
DOI: 10.1242/jeb.080960
|View full text |Cite
|
Sign up to set email alerts
|

Unique arylalkylamine N-acetyltransferase-2 polymorphism in Salmonids and profound variations in thermal stability and catalytic efficiency conferred by two residues

Abstract: SUMMARYMelatonin contributes to synchronizing major biological and behavioral functions with cyclic changes in the environment. Arylalkylamine N-acetyltransferase (AANAT) is responsible for a daily rhythm in melatonin secretion. Teleost possess two enzyme forms, AANAT1 and AANAT2, preferentially expressed in the retina and the pineal gland, respectively. The concomitant action of light and temperature shapes the daily and seasonal changes in melatonin secretion: the former controls duration while the latter mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…Aanat enzymes of vertebrates usually display a significantly higher catalytic efficiency for indolethylamines versus phenylethylamines . We bring here evidence that Aanat1 enzymes acetylated both indolethylamines and phenylethylamines in accordance with our previous findings in other species .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Aanat enzymes of vertebrates usually display a significantly higher catalytic efficiency for indolethylamines versus phenylethylamines . We bring here evidence that Aanat1 enzymes acetylated both indolethylamines and phenylethylamines in accordance with our previous findings in other species .…”
Section: Discussionsupporting
confidence: 90%
“…S2). These valine and isoleucine are involved in thermal stability and catalytic efficiency of teleost Aanat2 . In a thorough analysis of the available teleost's Aanat sequences, we found that these residues are highly conserved among teleost Aanat2 and, when not present, replaced by a valine while the corresponding lysine and methionine found in Aanat1a and Aanat1b are specific of this family and of Sarcopterygii Aanats.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The encoded proteins (206 and 207 aa) exhibited the two defining features of the GCN5 N-acetyltransferase superfamily, motifs A and B (SI Appendix, Fig. S1) (9,(22)(23)(24)(25)(26)(27)(28)(29). In addition, the sequences exhibited defining characteristics of the VT-AANATs of bony vertebrates, including motifs C and D, PKA sites nested in 14-3-3 binding domains, a Cys-ProLeu peptide sequence in a floppy loop within the binding region, and closely positioned histidine residues in the active site.…”
Section: Resultsmentioning
confidence: 99%
“…(iii) In cultured pineal organs, both cAMP production and AANAT activity display the same pattern in response to temperature; this is a species-dependent process (5). It is also a cellular-mediated process because the response of AANAT activity to temperature variation differs if measured on the native (ie, in situ) or recombinant enzymes (24,25). (iv) In mammals, temperature sensing is mediated by members of the Transient Receptor Potential (TRP) channels family (TRPA1, TRPV1-4 and TRPM8), which are permeable to Ca 2ϩ (26,27), and activate at different ranges of temperature (28).…”
mentioning
confidence: 99%